At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Wyatt claims that [tex]\(\sum_{n=0}^3\left(-\frac{1}{3}\right)^n \cdot 9\)[/tex] is equivalent to [tex]\(\sum_{n=0}^3 3^{2-n}\)[/tex]. Which statement about his claim is true?

A. True, because [tex]\(\left(-\frac{1}{3}\right)^n \cdot 9 = 3^{2-n}\)[/tex]
(Wyatt used properties of exponents to simplify the expression.)

B. True, because [tex]\(3^2\)[/tex] gives 9 and [tex]\(3^{-n}\)[/tex] will cause the signs to alternate
(Wyatt knows that negative exponents alternate the signs.)

C. False, because a base of [tex]\(\frac{1}{3}\)[/tex] and 9 cannot be combined into a single base for a power
(It does not matter that Wyatt dropped the negative.)

D. False, because when combined in this manner, the alternating signs of the series are lost
(Wyatt ignored the negative in the first factor.)


Sagot :

To determine which statement about Wyatt's claim is correct, let's analyze both series step-by-step.

Wyatt's claim is that:
[tex]\[ \sum_{n=0}^3\left(-\frac{1}{3}\right)^n \cdot 9 = \sum_{n=0}^3 3^{2-n}. \][/tex]

### Series 1: [tex]\(\sum_{n=0}^3\left(-\frac{1}{3}\right)^n \cdot 9\)[/tex]

We will expand this series term by term:
[tex]\[ \begin{align*} \left(-\frac{1}{3}\right)^0 \cdot 9 & = 1 \cdot 9 = 9, \\ \left(-\frac{1}{3}\right)^1 \cdot 9 & = -\frac{1}{3} \cdot 9 = -3, \\ \left(-\frac{1}{3}\right)^2 \cdot 9 & = \left(\frac{1}{9}\right) \cdot 9 = 1, \\ \left(-\frac{1}{3}\right)^3 \cdot 9 & = -\left(\frac{1}{27}\right) \cdot 9 = -\frac{1}{3}. \end{align*} \][/tex]

Adding these together:
[tex]\[ 9 - 3 + 1 - \frac{1}{3}. \][/tex]

Simplifying the result:
[tex]\[ 9 - 3 + 1 - \frac{1}{3} = 6 + 1 - \frac{1}{3} = 7 - \frac{1}{3} = \frac{21}{3} - \frac{1}{3} = \frac{20}{3}. \][/tex]

### Series 2: [tex]\(\sum_{n=0}^3 3^{2-n}\)[/tex]

We will expand this series term by term:
[tex]\[ \begin{align*} 3^{2-0} & = 3^2 = 9, \\ 3^{2-1} & = 3^1 = 3, \\ 3^{2-2} & = 3^0 = 1, \\ 3^{2-3} & = 3^{-1} = \frac{1}{3}. \end{align*} \][/tex]

Adding these together:
[tex]\[ 9 + 3 + 1 + \frac{1}{3}. \][/tex]

Simplifying the result:
[tex]\[ 9 + 3 + 1 + \frac{1}{3} = 13 + \frac{1}{3} = \frac{39}{3} + \frac{1}{3} = \frac{40}{3}. \][/tex]

### Comparing Results:

- From Series 1, we found that:
[tex]\[ \sum_{n=0}^3\left(-\frac{1}{3}\right)^n \cdot 9 = \frac{20}{3}. \][/tex]

- From Series 2, we found that:
[tex]\[ \sum_{n=0}^3 3^{2-n} = \frac{40}{3}. \][/tex]

Comparing [tex]\(\frac{20}{3}\)[/tex] and [tex]\(\frac{40}{3}\)[/tex], we see that they are not equal:
[tex]\[ \frac{20}{3} \neq \frac{40}{3}. \][/tex]

### Conclusion:

The statement regarding Wyatt's claim being equivalent is false. This means that the correct statement about Wyatt's claim is:

false, because a base of [tex]\(\frac{1}{3}\)[/tex] and 9 cannot be combined into a single base for a power (It does not matter that Wyatt dropped the negative.)